Lipid Abnormalities in the Natural History of Diabetes - Rahman, Muhammad Hafizur; Ali, Liaquat (Journal of Medicine, 2015)
Objective: To explore lipid abnormalities in normoglycemic first-degree diabetic relatives (FDRs) and prediabetic and diabetic subjects in the natural history of diabetes. Research design and methods: Thirty six impaired fasting glucose (IFG), 61 isolated impaired glucose tolerance (I-IGT), 64 combined IFG-IGT, 73 diabetic, and 32 FDRs along with 57 normoglycemic healthy controls without family history of diabetes in 1st degree relatives, were selected purposively following 2003 ADA cut-off values and 2006 WHO/IDF grouping. Anthropometry and blood pressure of the subjects were taken. Fasting and 2-h plasma glucose and HbA1C were measured. Fasting plasma triglyceride, total cholesterol and HDL cholesterol were measured by enzymatic colorimetric method. Results: Serum triglyceride was higher in IFG, I-IGT, IFG-IGT, diabetic and FDRs compared to Control [145 (59- 307), 128 (66-584), 166 (68-764), 161 (69-750) and 130 (81-281) vs. 108 (47-219) mg/dl, P<0.01, P<0.01, P<0.001, P<0.001 and P<0.05]. Total cholesterol was raised in IFG-IGT and diabetes compared to Control [185 (105-310), 185 (123-326) vs. 171 (101-235) mg/dl, P<0.05] and FDRs. But HDL did not differ among the groups. Prevalence of metabolic syndrome was higher in IFG, I-IGT, IFG-IGT and diabetes and FDRs than Control [55%, 38%, 57%, 58% and 36% vs. 15%, P<0.001, P<0.01, P<0.001, P<0.001 and P<0.05] and also in IFGIGT and diabetic compared to I-IGT and FDRs (P<0.05). Conclusions: Higher prevalence of metabolic syndrome and raised serum triglyceride is seen among diabetic, prediabetic and 1st degree diabetic-relatives. Total cholesterol and non-HDL cholesterol is raised only in IFG-IGT and diabetes, the more decompensated glycemic states. J MEDICINE July 2015; 16 (2) : 83-88